Governance Quality and Foreign direct Investments in Central and Eastern Europe : Macro-level Analysis Using Panel Data Approach - Kurach, Radosław (Jakość rządzenia (governance) i bezpośrednie inwestycje zagraniczne w krajach Europy Środkowo-Wschodniej : analiza makro-ekonomiczna z wykorzystaniem danych panelowych, 2010)
In this paper we investigate the role of governance quality in attracting foreign direct investments (FDIs) in the selected CEE states. Using panel data the fixed and random effects models are employed to assess the importance within and between country differences in governance quality. The obtained results indicate that the quality governance improvement over the last years has significantly affected the FDIs inflows to the CEE region, while the governance differences between the selected countries do not explain the intercountry differences in FDIs.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 136, s. 62-72
Keywords: foreign direct investments; governance; fixed and random effects models